2010
DOI: 10.1521/jaap.2010.38.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamics of Hypersexuality in Children and Adolescents with Bipolar Disorder

Abstract: It has recently become evident that bipolar disorder exists in children and adolescents. The criteria for making the diagnosis of juvenile bipolar disorder (JBD) are in the process of being proposed for the fifth edition of the Diagnostic and Statistical Manual (DSM-V). In adults, a criterion for bipolar disorder is excessive involvement in pleasurable activities including hypersexuality. Recently, some clinicians and researchers have suggested that hypersexuality be included as a criterion for JBD as well. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In addition, the duration criteria for JBD present unique difficulties due to the preponderance of rapidly cycling and mixed states in youth with possible bipolar symptoms. Very rapidly cycling mood states lasting as little as four hours ("ultradian" cycling) has been found frequently; such brief cycles, which verge on the length of severe tantrums, may be clinically difficult to distinguish from maladaptive coping strategies in dysfunctional environments (Adelson, 2010;McClellan, Kowatch, Findling, & Work Group on Quality Issues, 2007).…”
Section: Controversies In Defining Juvenile Bipolar Disordermentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the duration criteria for JBD present unique difficulties due to the preponderance of rapidly cycling and mixed states in youth with possible bipolar symptoms. Very rapidly cycling mood states lasting as little as four hours ("ultradian" cycling) has been found frequently; such brief cycles, which verge on the length of severe tantrums, may be clinically difficult to distinguish from maladaptive coping strategies in dysfunctional environments (Adelson, 2010;McClellan, Kowatch, Findling, & Work Group on Quality Issues, 2007).…”
Section: Controversies In Defining Juvenile Bipolar Disordermentioning
confidence: 99%
“…For example, youth who display symptoms consistent with diagnoses of both bipolar disorder and ADHD would merit the diagnosis of bipolar disorder if it could be shown that the symptoms predict adult bipolar disorder in adulthood, and are characterized by biological markers such as genetic patterns shared with adult bipolar family members (Adelson, 2010). The predictive value of the current criteria of bipolar disorder in affectively dysregulated youth has not yet been definitively established (Leibenluft, 2011).…”
Section: Controversies In Defining Juvenile Bipolar Disordermentioning
confidence: 99%
See 3 more Smart Citations